Food additives – risk analysis and legislation - Stanković, Ivan; Zrnić Ćirić, Milica (Archives of Pharmacy, 2021)
Food additive is any substance not normally consumed as a food, the intentional addition of which to food for a technological purpose results in it or its by-products becoming a component of such foods. The use of each new additive is preceded by a risk analysis consisting of three interrelated components: risk assessment, risk management and risk communication. At the international level in the Codex Alimentarius system, risk assessment is performed by the Joint (FAO/WHO) Expert Committee on Food Additives (JECFA) and risk management by Codex Alimentarius Commission (CAC) that, based on the results of the risk assessment, prepares international standards and recommendations that Member States incorporate into national regulations. At the level of the European Union (EU), risk assessment is performed by the European Food Safety Authority (EFSA) as a basis for risk management by the European Commission (EC) that prepares food additive legislation, and member states authorities responsible for official control of additives on the market. Risk communication takes place between all stakeholders including academia, food producers and consumers. The regulation on additives in the Republic of Serbia is fully harmonized with the EU legislation in this area.